Macroprudential Policy : An Organizing Framework. (Policy Papers; Policy Paper ;, 2011)
Macroprudential policy is a complement to microprudential policy and it interacts with other types of public policy that have an impact on systemic financial stability. Indeed, prudential regulation, as carried out in the past, also had some macroprudential aspects, and the recent crisis has reinforced this focus; hence, a clear separation between 'micro' and 'macro' prudential, if useful conceptually, is difficult to delineate in practice. Moreover, no matter how different policy mandates are structured, financial stability tends to be a common responsibility, reflecting the far reaching consequences of financial crises. This calls for coordination across policies, to ensure that systemic risk is comprehensively addressed. Equally important, macroprudential policy is no substitute for sound policies more broadly, including, in particular, strong prudential regulation and supervision, and sound macroeconomic policies. Operational independence in other policy areas, including monetary and microprudential policy, should not be undermined in the name of macroprudential policy. Finally, given the global nature of the financial system, the multilateral aspects of macroprudential policy will need to be fully considered-an important aspect that is only touched upon in this paper.